Seni Mural Di Kecamatan Majalaya: Tinjauan Filsafat Seni Leo Tolstoy - Kurnia, Tiara Rahma (Jurnal Riset Agama, 2021)
The purpose of this study was to analyze mural art in Majalaya sub-district in terms of the art philosophy of Leo Tolstoy. This study uses a qualitative approach with the type of field research. The results and discussion of this reseach include mural art in Majalaya District, Leo Tolstoy philosophy of art, and analysis of mural art in Majalaya District in terms of Leo Tolstoy art philosophy. The conclusion of this study is that mural art in Majalaya District in terms of principles and practice is relevant to Leo Tolstoy’s philosophy of art. The research is recommended for further and in-depth research on mural art and other arts in order to support its existence, especially in Majalaya District.